Selection of Operative Procedures for Cubital Tunnel Syndrome - Novak, Christine B. (Springer-Verlag, 2008)
The purpose of this study was to investigate the primary operative procedures that are performed by hand surgeons for cubital tunnel syndrome and their reported satisfaction with these procedures. The survey consisted of 22 questions regarding primary operative treatment of cubital tunnel syndrome and demographics and was sent by email to the 459 active members of the American Association for Hand Surgery. One hundred sixty-four surgeons completed the survey (36% response rate). The total sample included 154 hand surgeons (143 males, 11 females) who operated on cubital tunnel syndrome and the majority of surgeons were in private practice (n = 100) followed by academic practice (n = 50). The most prevalent factors that influence the decision to operate include evidence of muscle atrophy (84%), abnormal nerve conduction studies (51%), and failed non-operative treatment (49%). Most surgeons (n = 133) reported using more than one operative procedure for their patients with cubital tunnel syndrome. Factors that influenced the operative procedure selected included the degree of nerve compression (60%), medical comorbidities (30%), patient’s occupation (28%), and obesity (22%). Following carpal tunnel surgery, 88% of the surgeons were “very satisfied” with their patient outcome and following surgery for cubital tunnel syndrome, only 44% were “very satisfied” with their patient outcome. Most surgeons use more than one operative procedure in their treatment of patients with cubital tunnel syndrome and the selection of the operative procedure is influenced by patient factors and surgeon preference.